Wear-resistant anticorrosive water-based zinc-rich paint and preparation method thereof

CN122255826BActive Publication Date: 2026-10-13GUOKE XIANCAI (HEFEI) TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202610574876.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-04-28
Publication Date
2026-10-13
Estimated Expiration
2046-04-28

AI Technical Summary

Technical Problem

[0004]本发明的目的在于提供一种耐磨防腐蚀水性富锌涂料及其制备方法,解决了以下几点技术问题:(1)普通的水性富锌涂料抗腐蚀效果单一,防腐蚀能力不足的问题;(2)普通的水性富锌涂料附着力、抗氧化能力以及耐磨性能有待提升的问题

Benefits of technology

[0025]本发明通过制备咖啡酸改性云母粉、糠基改性聚乙二醇与锌粉三者形成协同增效的防腐体系,通过咖啡酸改性云母粉的片状结构提供物理屏蔽层延缓腐蚀介质的渗透,降低锌粉消耗速率,糠基改性聚乙二醇以其疏水的呋喃基团阻隔锌粉与水分的直接接触,减少锌粉的无效消耗,显著增强了涂层的防腐蚀效果,同时体系中的邻苯二酚结构与醚键能够有效增强附着力,邻苯二酚结构还能够增强体系的抗氧化效果,咖啡酸改性云母粉的加入能够增强体系的耐磨能力,使得制备出来的涂料除了具有优异的防腐蚀效果之外,还具有良好的耐磨性能和优异的附着能力以及抗氧化效果,具有长久的使用寿命。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122255826B_ABST
    Figure CN122255826B_ABST
Patent Text Reader

Abstract

The application relates to the paint technology field and discloses a wear-resistant anticorrosive water-based zinc-rich paint and a preparation method thereof. The wear-resistant anticorrosive water-based zinc-rich paint is composed of two parts of component A and component B. The component A comprises the following raw materials: a water-based epoxy emulsion, coffee acid modified mica powder, furfuryl modified polyethylene glycol, carbon black and deionized water. The component B comprises the following raw materials: dimer acid type polyamide, zinc powder, a wetting agent, a defoaming agent, an anti-settling thixotropic agent and a cosolvent. The coffee acid modified mica powder and the furfuryl modified polyethylene glycol are prepared and used in the preparation process of the water-based zinc-rich paint, so that the prepared paint has excellent anticorrosive effect, good wear resistance, excellent adhesion and excellent oxidation resistance, and has a long service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of coating technology, specifically to a wear-resistant and corrosion-resistant water-based zinc-rich coating and its preparation method. Background Technology

[0002] Water-based zinc-rich coatings are water-dispersible coatings with extremely low volatile organic compound (VOC) content, offering significant environmental advantages. They utilize zinc powder as a sacrificial anode filler and employ a cathodic protection mechanism to provide long-lasting corrosion protection. They are widely used in heavy-duty corrosion protection fields such as shipbuilding, bridges, marine engineering, petrochemicals, and steel structures. However, in ordinary water-based zinc-rich coatings, the zinc powder density is significantly higher than in water-based resin systems. During storage and application, this can easily lead to sedimentation and agglomeration, resulting in uneven zinc powder distribution in the coating. This damages the continuity of the cathodic protection network, weakening the corrosion resistance. Furthermore, the interface between the water-based system and the metal substrate... The coating exhibits weak adhesion and poor bonding ability, especially in humid environments or high-temperature conditions. It is prone to peeling, blistering, and other failures from the substrate. Furthermore, most existing water-based zinc-rich coatings lack antioxidant capabilities and are prone to aging and degradation over long-term use, leading to yellowing, powdering, or even cracking of the coating and affecting its anti-corrosion effect. In addition, the resin base of existing water-based zinc-rich coatings has poor hardness and its wear resistance needs to be improved. When subjected to mechanical friction, the coating is prone to scratches and wear, resulting in local damage to the protective barrier, accelerating the penetration of corrosive media, and ultimately significantly shortening the service life of the anti-corrosion coating.

[0003] To address the aforementioned performance deficiencies, researchers have conducted various explorations and improvements. For example, patent CN117363157A discloses a water-based epoxy zinc-rich coating and its preparation method. The prepared coating has environmentally friendly properties and excellent anti-corrosion ability and adhesion. However, this patent does not improve the coating's anti-oxidation ability. Under prolonged humid and hot conditions, the coating is prone to oxidation and powdering, affecting the final anti-corrosion effect of the coating. Summary of the Invention

[0004] The purpose of this invention is to provide a wear-resistant and corrosion-resistant water-based zinc-rich coating and its preparation method, which solves the following technical problems: (1) the problem that ordinary water-based zinc-rich coatings have a single anti-corrosion effect and insufficient anti-corrosion ability; (2) the problem that the adhesion, anti-oxidation ability and wear resistance of ordinary water-based zinc-rich coatings need to be improved.

[0005] The objective of this invention can be achieved through the following technical solutions:

[0006] A wear-resistant and corrosion-resistant water-based zinc-rich coating comprises two parts, component A and component B. Component A includes the following raw materials in parts by weight: 50-80 parts water-based epoxy emulsion, 2-3 parts caffeic acid-modified mica powder, 1.5-2.5 parts furfuryl-modified polyethylene glycol, 0.5-1 part carbon black, and 15-25 parts deionized water. Component B includes the following raw materials in parts by weight: 10-15 parts dimer acid type polyamide, 35-40 parts zinc powder, 0.3-0.5 parts wetting agent, 0.5-0.8 parts defoamer, 0.5-1 part anti-settling thixotropic agent, and 4-8 parts co-solvent. The caffeic acid-modified mica powder is prepared by reacting epoxy-grafted mica powder with caffeic acid. The epoxy-grafted mica powder is prepared by surface modification of mica powder with a silane coupling agent. The furfuryl-modified polyethylene glycol is prepared by reacting acrylate-polyethylene glycol-hydroxyl with furfuryl thiol.

[0007] Further, the epoxy equivalent of the aqueous epoxy emulsion is 400-600 g / eq; the wetting agent is any one of Tween 80 and polyether-modified polydimethylsiloxane; the defoamer is any one of dimethyl silicone oil defoamer and polyether-modified polysiloxane defoamer; the anti-settling thixotropic agent is any one of polyamide wax powder, organobentonite, and fumed silica; and the co-solvent is any one of propylene glycol methyl ether, dipropylene glycol butyl ether, and dodecyl alcohol ester.

[0008] Furthermore, the preparation method of the caffeic acid-modified mica powder includes the following steps:

[0009] S1: Place silane coupling agent KH-560 in anhydrous ethanol and stir thoroughly. Add mica powder, purge with nitrogen, and ultrasonically disperse for 15-20 min. Then, heat in an oil bath and reflux with stirring. Filter, dry in an oven at 110-120℃ for 0.5-1 h, cool, and pass through a 200-300 mesh sieve to obtain epoxy-grafted mica powder.

[0010] S2: Place epoxy-grafted mica powder in N,N-dimethylformamide, introduce nitrogen gas, and ultrasonically disperse for 18-25 min. Then add caffeic acid and catalyst, heat to 80-90℃ and react for 4-6 h. After filtration, wash with anhydrous ethanol 3-5 times and deionized water 2-4 times. After vacuum drying, collect the product to obtain caffeic acid modified mica powder.

[0011] Through the above technical solution, the surface of mica powder is modified using the silane coupling agent KH-560, grafting epoxy groups onto the mica powder surface to obtain epoxy-grafted mica powder. Then, under the action of a catalyst, the epoxy groups in the epoxy-grafted mica powder structure undergo a ring-opening reaction with the carboxyl groups in the caffeic acid structure to obtain caffeic acid-modified mica powder. In this caffeic acid-modified mica powder structure, small caffeic acid molecules are chemically bonded to the mica surface, effectively enhancing the connection between caffeic acid and the matrix, making it less prone to migration and failure during long-term use. Simultaneously, the catechol structure in its structure significantly enhances its ability to bind to the matrix. It enhances the adhesion between the coating and the substrate, and exerts a free radical scavenging effect, inhibiting the oxidative degradation of epoxy resin and improving the anti-oxidation effect of the coating. In addition, mica powder has a lamellar structure, and after grafting modification, the active hydroxyl groups on the surface can participate in the curing process of epoxy resin, enhancing interfacial compatibility and making it more uniformly dispersed in the coating to form a dense physical shielding layer. This shielding layer and the cathodic protection effect of zinc powder produce a synergistic effect, effectively blocking the penetration of corrosive media, reducing the consumption rate of zinc powder, and enhancing the wear resistance of the coating, effectively improving the service life of the coating.

[0012] Furthermore, in step S1, the oil bath heating and reflux stirring reaction time is 1-2 hours.

[0013] Further, in step S2, the catalyst is any one of tetrabutylammonium bromide, tetrabutylammonium chloride, tetrabutylammonium hydroxide, and tetrabutylammonium bisulfate.

[0014] Furthermore, the preparation method of the furfural-modified polyethylene glycol includes the following steps:

[0015] Acrylate-polyethylene glycol-hydroxyl and furfuryl thiol were placed in anhydrous dimethyl sulfoxide, nitrogen gas was introduced, a photoinitiator was added, and the mixture was irradiated under a UV lamp for 1-2 hours. After the reaction was completed, the reaction solution was dropped into diethyl ether to precipitate the precipitate. The precipitate was collected by centrifugation, washed, and vacuum dried to obtain furfuryl-modified polyethylene glycol.

[0016] Through the above technical solution, under the action of photoinitiator and ultraviolet lamp, the alkenyl group in the acrylate-polyethylene glycol-hydroxyl structure and the mercapto group in the furfuryl thiol structure undergo a click reaction to obtain furfuryl-modified polyethylene glycol. The multiple ether bonds in this furfuryl-modified polyethylene glycol structure can form hydrogen bonds with the surface of the metal substrate, and produce a synergistic effect with the catechol structure in the caffeic acid-modified mica powder structure, enhancing the adhesion between the coating and the substrate. At the same time, the hydroxyl groups at the end of the chain segments can participate in the epoxy resin curing reaction process, embedding the furfuryl group into the cross-linking network in a chemical bonding manner, effectively avoiding the migration of small molecules. The introduced furan groups have high electron cloud density and hydrophobic properties, which can be adsorbed on the metal surface to form a barrier layer, helping to maintain the dry environment of the zinc powder surface, reducing the direct contact between zinc powder and water, inhibiting the ineffective consumption of zinc powder, thereby enhancing the corrosion effect of the coating. This makes the prepared coating material have excellent anti-corrosion ability and can meet the needs of use in various environments.

[0017] Furthermore, the photoinitiator is any one of benzoin dimethyl ether, 2-hydroxy-2-methyl-1-phenyl-1-propanone, and 1-hydroxycyclohexylphenyl ketone.

[0018] Furthermore, the wavelength of the ultraviolet lamp is 300-400nm.

[0019] A method for preparing a wear-resistant and corrosion-resistant water-based zinc-rich coating includes the following steps:

[0020] Step 1: Mix the water-based epoxy emulsion, caffeic acid modified mica powder, furfuryl modified polyethylene glycol, carbon black, and deionized water thoroughly at 300-400 rpm for 1-1.5 hours to obtain coating component A.

[0021] Step 2: Mix dimer acid polyamide, zinc powder, wetting agent, defoamer, anti-settling thixotropic agent, and cosolvent, and disperse evenly at a speed of 500-600 rpm to obtain coating component B;

[0022] Step 3: Mix component A and component B of the coating at a mass ratio of 1:0.6-0.8 until homogeneous to obtain the water-based zinc-rich coating.

[0023] Furthermore, in step two, the zinc powder has a fineness of 500-600 mesh.

[0024] The beneficial effects of this invention are:

[0025] This invention prepares a synergistic anti-corrosion system by combining caffeic acid-modified mica powder, furfuryl-modified polyethylene glycol, and zinc powder. The flake-like structure of the caffeic acid-modified mica powder provides a physical shielding layer to delay the penetration of corrosive media and reduce the consumption rate of zinc powder. The furfuryl-modified polyethylene glycol, with its hydrophobic furan groups, blocks direct contact between zinc powder and moisture, reducing ineffective consumption of zinc powder and significantly enhancing the anti-corrosion effect of the coating. At the same time, the catechol structure and ether bonds in the system effectively enhance adhesion, and the catechol structure also enhances the antioxidant effect of the system. The addition of caffeic acid-modified mica powder enhances the wear resistance of the system. As a result, the prepared coating not only has excellent anti-corrosion effect, but also good wear resistance, excellent adhesion, and antioxidant effect, resulting in a long service life.

[0026] Of course, any product implementing this invention does not necessarily need to achieve all of the advantages described above at the same time. Attached Figure Description

[0027] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0028] Figure 1 This is a flowchart illustrating the preparation process of the wear-resistant and corrosion-resistant water-based zinc-rich coating of the present invention. Detailed Implementation

[0029] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0030] The preparation methods of caffeic acid-modified mica powder and furfural-modified polyethylene glycol in the following embodiments and comparative examples of the present invention are as follows:

[0031] I. Preparation of Caffeic Acid Modified Mica Powder

[0032] S1: Place 1g of silane coupling agent KH-560 in 10ml of anhydrous ethanol and stir thoroughly. Add 3g of mica powder, purge with nitrogen, and ultrasonically disperse for 15min. Then, heat in an oil bath and reflux with stirring for 1h. Filter, dry in an oven at 110℃ for 0.5h, cool, and pass through a 200-mesh sieve to obtain epoxy-grafted mica powder.

[0033] S2: Place 3g of epoxy-grafted mica powder in 60ml of N,N-dimethylformamide, purge with nitrogen, and sonicate for 18min. Then add 0.8g of caffeic acid and 0.02g of tetrabutylammonium bromide, heat to 80℃ and react for 4h. After filtration, wash 3 times with anhydrous ethanol and 2 times with deionized water. After vacuum drying, collect the product to obtain caffeic acid-modified mica powder.

[0034] The epoxy value of epoxy-grafted mica powder and caffeic acid-modified mica powder was tested using the hydrochloric acid-acetone method. 1g of each sample was taken and tested according to the following steps: 1g sample was placed in a 150ml iodine flask, and 25ml of 0.1mol / L hydrochloric acid-acetone solution was added. After thorough mixing, the mixture was left at room temperature for 30min, shaking every 5min. Two drops of bromothymol blue indicator were added, and titration was performed with 0.1mol / L sodium hydroxide-ethanol solution until the solution changed color. The volume consumed, V1, was recorded. A blank test was also performed, and the volume consumed, V0, was recorded. The epoxy value (mol / L) was calculated using the following formula: 100g) = (V0-V1)C×0.1 / m; where V0 is the volume of sodium hydroxide-ethanol solution consumed in the blank test, ml; V1 is the volume of sodium hydroxide-ethanol solution consumed by the sample, ml; C is the standard concentration of sodium hydroxide-ethanol solution, mol / L; m is the sample mass, g; 0.1 is the unit conversion factor; after calculation, the epoxy value of epoxy-grafted mica powder is 0.12mol / 100g; the epoxy value of caffeic acid modified mica powder is 0.04mol / 100g; it can be seen that the epoxy value of epoxy-grafted mica powder is significantly higher than that of caffeic acid modified mica powder, which is due to the reaction between the epoxy groups in epoxy-grafted mica powder and the carboxyl groups in the caffeic acid structure.

[0035] II. Preparation of furfuryl-modified polyethylene glycol

[0036] 4.5g of acrylate-polyethylene glycol-hydroxyl and 1.2g of furfuryl thiol were placed in 50ml of anhydrous dimethyl sulfoxide, nitrogen gas was introduced, and 0.1g of benzoin dimethyl ether was added. The mixture was irradiated under a UV lamp with a wavelength of 365nm for 1h. After the reaction was completed, the reaction solution was dropped into 200ml of diethyl ether to precipitate. The precipitate was collected by centrifugation, washed, and vacuum dried to obtain furfuryl-modified polyethylene glycol.

[0037] The sulfur content in the sample was analyzed using an elemental analyzer. The analysis showed that there was no sulfur in the acrylate-polyethylene glycol-hydroxyl group; the sulfur content in the furfuryl-modified polyethylene glycol was 0.32%. The presence of sulfur was due to the reaction between the double bond in the acrylate-polyethylene glycol-hydroxyl structure and the thiol group in the furfuryl mercaptan structure.

[0038] The double bond content in acrylate-polyethylene glycol-hydroxy and furfuryl-modified polyethylene glycol was tested using the bromination method. acrylate-polyethylene glycol-hydroxy and furfuryl-modified polyethylene glycol were used as samples, and the following steps were followed: 0.3 g of sample was placed in an iodine flask, 10 ml of distilled water was added and mixed well, then 10 ml of potassium bromate-potassium bromide solution (0.1 mol / L potassium bromate + excess potassium bromide) was added, followed by 5 ml of 6 mol / L hydrochloric acid solution. The mixture was shaken well and placed in the dark for 30 min. Then, 10 ml of 10% potassium iodide solution was added, and titration was performed with 0.1 mol / L sodium thiosulfate solution until the solution color changed. Starch indicator was added and titration continued. The test was continued until the blue color disappeared, and a blank test was performed simultaneously. The double bond content in the sample was calculated using the following formula: Double bond content (mmol / g) = (V0-V1)C / 2m, where V0 is the volume of sodium thiosulfate solution consumed by the sample in the blank test (ml); V1 is the volume of sodium thiosulfate solution consumed by the sample (ml); C is the concentration of sodium thiosulfate solution (mol / L); and m is the sample mass (g). The calculated double bond content in acrylate-polyethylene glycol-hydroxyl was 0.12 mmol / g, and the double bond content in furfuryl-modified polyethylene glycol was 0.02 mmol / g. The decrease was due to the reaction between the double bond in the acrylate-polyethylene glycol-hydroxyl structure and the thiol group in the furfuryl thiol structure.

[0039] Example 1

[0040] Preparation of water-based zinc-rich coatings

[0041] Step 1: Mix 50 parts of waterborne epoxy emulsion with an epoxy equivalent of 400 g / eq, 2 parts of caffeic acid modified mica powder, 1.5 parts of furfuryl modified polyethylene glycol, 0.5 parts of carbon black, and 15 parts of deionized water thoroughly at 300 rpm for 1 hour to obtain coating component A.

[0042] Step 2: Mix 10 parts of dimer acid type polyamide, 35 parts of zinc powder with a fineness of 500 mesh, 0.3 parts of wetting agent Tween 80, 0.5 parts of dimethyl silicone oil defoamer, 0.5 parts of anti-settling thixotropic agent polyamide wax powder, and 4 parts of cosolvent propylene glycol methyl ether, and disperse evenly at a speed of 500 rpm to obtain coating component B.

[0043] Step 3: Mix component A and component B of the coating at a mass ratio of 1:0.6 until homogeneous to obtain the water-based zinc-rich coating.

[0044] Example 2

[0045] Preparation of water-based zinc-rich coatings

[0046] Step 1: Mix 65 parts of waterborne epoxy emulsion with an epoxy equivalent of 500 g / eq, 2.5 parts of caffeic acid modified mica powder, 2 parts of furfural modified polyethylene glycol, 0.8 parts of carbon black, and 20 parts of deionized water thoroughly at 350 rpm for 1.2 h to obtain coating component A.

[0047] Step 2: Mix 12 parts of dimer acid type polyamide, 38 parts of zinc powder with a fineness of 550 mesh, 0.4 parts of wetting agent polyether modified polydimethylsiloxane, 0.6 parts of dimethyl silicone oil defoamer, 0.8 parts of anti-settling thixotropic agent organic bentonite, and 6 parts of cosolvent dipropylene glycol butyl ether, and disperse evenly at a speed of 550 rpm to obtain coating component B;

[0048] Step 3: Mix component A and component B of the coating at a mass ratio of 1:0.7 until homogeneous to obtain the water-based zinc-rich coating.

[0049] Example 3

[0050] Preparation of water-based zinc-rich coatings

[0051] Step 1: Mix 80 parts of waterborne epoxy emulsion with an epoxy equivalent of 600 g / eq, 3 parts of caffeic acid modified mica powder, 2.5 parts of furfuryl modified polyethylene glycol, 1 part of carbon black, and 25 parts of deionized water thoroughly at 400 rpm for 1.5 h to obtain coating component A.

[0052] Step 2: Mix 15 parts of dimer acid type polyamide, 40 parts of zinc powder with a fineness of 600 mesh, 0.5 parts of wetting agent Tween 80, 0.8 parts of polyether modified polysiloxane defoamer, 1 part of anti-settling thixotropic agent fumed silica, and 8 parts of cosolvent dodecyl alcohol ester, and disperse evenly at a speed of 600 rpm to obtain coating component B;

[0053] Step 3: Mix component A and component B of the coating at a mass ratio of 1:0.8 until homogeneous to obtain the water-based zinc-rich coating.

[0054] Comparative Example 1

[0055] Preparation of water-based zinc-rich coatings

[0056] Step 1: Mix 65 parts of waterborne epoxy emulsion with an epoxy equivalent of 500 g / eq, 2 parts of furfural-modified polyethylene glycol, 0.8 parts of carbon black, and 20 parts of deionized water thoroughly at 350 rpm for 1.2 h to obtain coating component A.

[0057] Step 2: Mix 12 parts of dimer acid type polyamide, 38 parts of zinc powder with a fineness of 550 mesh, 0.4 parts of wetting agent polyether modified polydimethylsiloxane, 0.6 parts of dimethyl silicone oil defoamer, 0.8 parts of anti-settling thixotropic agent organic bentonite, and 6 parts of cosolvent dipropylene glycol butyl ether, and disperse evenly at a speed of 550 rpm to obtain coating component B;

[0058] Step 3: Mix component A and component B of the coating at a mass ratio of 1:0.7 until homogeneous to obtain the water-based zinc-rich coating.

[0059] Comparative Example 2

[0060] Preparation of water-based zinc-rich coatings

[0061] Step 1: Mix 65 parts of waterborne epoxy emulsion with an epoxy equivalent of 500 g / eq, 2.5 parts of caffeic acid modified mica powder, 0.8 parts of carbon black, and 20 parts of deionized water thoroughly at 350 rpm for 1.2 h to obtain coating component A.

[0062] Step 2: Mix 12 parts of dimer acid type polyamide, 38 parts of zinc powder with a fineness of 550 mesh, 0.4 parts of wetting agent polyether modified polydimethylsiloxane, 0.6 parts of dimethyl silicone oil defoamer, 0.8 parts of anti-settling thixotropic agent organic bentonite, and 6 parts of cosolvent dipropylene glycol butyl ether, and disperse evenly at a speed of 550 rpm to obtain coating component B;

[0063] Step 3: Mix component A and component B of the coating at a mass ratio of 1:0.7 until homogeneous to obtain the water-based zinc-rich coating.

[0064] Comparative Example 3

[0065] Preparation of water-based zinc-rich coatings

[0066] Step 1: Mix 65 parts of waterborne epoxy emulsion with an epoxy equivalent of 500 g / eq, 2.5 parts of epoxy-grafted mica powder, 2 parts of furfural-modified polyethylene glycol, 0.8 parts of carbon black, and 20 parts of deionized water thoroughly at 350 rpm for 1.2 h to obtain coating component A.

[0067] Step 2: Mix 12 parts of dimer acid type polyamide, 38 parts of zinc powder with a fineness of 550 mesh, 0.4 parts of wetting agent polyether modified polydimethylsiloxane, 0.6 parts of dimethyl silicone oil defoamer, 0.8 parts of anti-settling thixotropic agent organic bentonite, and 6 parts of cosolvent dipropylene glycol butyl ether, and disperse evenly at a speed of 550 rpm to obtain coating component B;

[0068] Step 3: Mix component A and component B of the coating at a mass ratio of 1:0.7 until homogeneous to obtain the water-based zinc-rich coating.

[0069] Comparative Example 4

[0070] Preparation of water-based zinc-rich coatings

[0071] Step 1: Mix 65 parts of waterborne epoxy emulsion with an epoxy equivalent of 500 g / eq, 2.5 parts of caffeic acid modified mica powder, 2 parts of acrylate-polyethylene glycol-hydroxyl, 0.8 parts of carbon black, and 20 parts of deionized water thoroughly at 350 rpm for 1.2 h to obtain coating component A.

[0072] Step 2: Mix 12 parts of dimer acid type polyamide, 38 parts of zinc powder with a fineness of 550 mesh, 0.4 parts of wetting agent polyether modified polydimethylsiloxane, 0.6 parts of dimethyl silicone oil defoamer, 0.8 parts of anti-settling thixotropic agent organic bentonite, and 6 parts of cosolvent dipropylene glycol butyl ether, and disperse evenly at a speed of 550 rpm to obtain coating component B;

[0073] Step 3: Mix component A and component B of the coating at a mass ratio of 1:0.7 until homogeneous to obtain the water-based zinc-rich coating.

[0074] Performance testing

[0075] Referring to standard GB / T1727-2021, the water-based zinc-rich coatings prepared in Examples 1-3 and Comparative Examples 1-4 were uniformly coated onto carbon steel test plates conforming to specifications using a brush coating method. The dry film thickness was controlled at 80±10μm. After curing, these were used as samples. Referring to standard GB / T9751.1-2008, the viscosity of the samples was tested. Referring to standard GB / T9286-2021, the adhesion grade of the samples and the samples treated in an aging chamber at 70% humidity and 80℃ for 72 hours was evaluated to determine... The samples were tested for oxidation resistance and adhesion. Salt spray resistance was tested according to standard GB / T10125-2021, involving continuous spraying in a 5% sodium chloride solution at 35±2℃. The time it took for the coating to show signs of rust, blistering, or peeling was recorded to determine the sample's corrosion resistance. The surface resistivity was tested according to standard GB / T31838.2-2019 to evaluate the effectiveness of the zinc powder conductive network. Hardness was tested according to standard GB / T6739-2022 to determine the sample's wear resistance. Specific test results are shown in the table below.

[0076] As shown in the table above, the viscosity of the samples prepared in Examples 1-3 of this invention is significantly lower than that of the comparative example. The coatings have good dispersibility, and the adhesion grade of the coatings is 0. Even after wet heat aging, the adhesion grade remains at 0, demonstrating excellent oxidation resistance and adhesion. The salt spray resistance time is as high as 2800 hours, and the surface resistivity is as low as 10. 3 The zinc-rich coating prepared by this invention has excellent anti-corrosion ability, superior adhesion, wear resistance and oxidation resistance, and a long service life. The hardness of the pencil is 2H, which is significantly better than that of the comparative example.

[0077] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.

[0078] The above content is merely an example and illustration of the concept of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described or use similar methods to replace them, as long as they do not deviate from the scope defined by the inventive concept, they should all fall within the protection scope of the present invention.

Claims

1. A wear-resistant and corrosion-resistant water-based zinc-rich coating, characterized in that, It consists of two parts, component A and component B. Component A includes the following raw materials in parts by weight: 50-80 parts of waterborne epoxy emulsion, 2-3 parts of caffeic acid modified mica powder, 1.5-2.5 parts of furfuryl modified polyethylene glycol, 0.5-1 part of carbon black, and 15-25 parts of deionized water. Component B includes the following raw materials in parts by weight: 10-15 parts of dimer acid type polyamide, 35-40 parts of zinc powder, 0.3-0.5 parts of wetting agent, 0.5-0.8 parts of defoamer, 0.5-1 part of anti-settling thixotropic agent, and 4-8 parts of cosolvent. The mass ratio of component A to component B is 1:0.6-0.

8. The preparation method of the coffee acid-modified mica powder includes the following steps: S1: Place silane coupling agent KH-560 in anhydrous ethanol and stir thoroughly. Add mica powder, purge with nitrogen, and ultrasonically disperse for 15-20 min. Then, heat in an oil bath and reflux with stirring. Filter, dry in an oven at 110-120℃ for 0.5-1 h, cool, and pass through a 200-300 mesh sieve to obtain epoxy-grafted mica powder. S2: Place epoxy-grafted mica powder in N,N-dimethylformamide, introduce nitrogen gas, ultrasonically disperse for 18-25 min, add caffeic acid and catalyst, heat to 80-90℃ and react for 4-6 h, filter, wash with anhydrous ethanol 3-5 times, wash with deionized water 2-4 times, vacuum dry and collect the product to obtain caffeic acid modified mica powder. The preparation method of the furfural-modified polyethylene glycol includes the following steps: Acrylate-polyethylene glycol-hydroxyl and furfuryl thiol were placed in anhydrous dimethyl sulfoxide, nitrogen gas was introduced, a photoinitiator was added, and the mixture was irradiated under a UV lamp for 1-2 hours. After the reaction was completed, the reaction solution was dropped into diethyl ether to precipitate the precipitate. The precipitate was collected by centrifugation, washed, and vacuum dried to obtain furfuryl-modified polyethylene glycol.

2. The wear-resistant and corrosion-resistant water-based zinc-rich coating according to claim 1, characterized in that, The epoxy equivalent of the aqueous epoxy emulsion is 400-600 g / eq; the wetting agent is any one of Tween 80 and polyether-modified polydimethylsiloxane; the defoamer is any one of dimethyl silicone oil defoamer and polyether-modified polysiloxane defoamer; the anti-settling thixotropic agent is any one of polyamide wax powder, organobentonite, and fumed silica; and the co-solvent is any one of propylene glycol methyl ether, dipropylene glycol butyl ether, and dodecyl alcohol ester.

3. The wear-resistant and corrosion-resistant water-based zinc-rich coating according to claim 1, characterized in that, In step S1, the oil bath heating and reflux stirring reaction time is 1-2 hours.

4. The wear-resistant and corrosion-resistant water-based zinc-rich coating according to claim 1, characterized in that, In step S2, the catalyst is any one of tetrabutylammonium bromide, tetrabutylammonium chloride, tetrabutylammonium hydroxide, and tetrabutylammonium bisulfate.

5. The wear-resistant and corrosion-resistant water-based zinc-rich coating according to claim 1, characterized in that, The photoinitiator is any one of benzoin dimethyl ether, 2-hydroxy-2-methyl-1-phenyl-1-propanone, and 1-hydroxycyclohexylphenyl ketone.

6. The wear-resistant and corrosion-resistant water-based zinc-rich coating according to claim 1, characterized in that, The wavelength of the ultraviolet lamp is 300-400nm.

7. The method for preparing a wear-resistant and corrosion-resistant water-based zinc-rich coating as described in claim 1, characterized in that, Includes the following steps: Step 1: Mix the water-based epoxy emulsion, caffeic acid modified mica powder, furfuryl modified polyethylene glycol, carbon black, and deionized water thoroughly at 300-400 rpm for 1-1.5 hours to obtain coating component A. Step 2: Mix dimer acid polyamide, zinc powder, wetting agent, defoamer, anti-settling thixotropic agent, and cosolvent, and disperse evenly at a speed of 500-600 rpm to obtain coating component B; Step 3: Mix component A and component B of the coating at a mass ratio of 1:0.6-0.8 until homogeneous to obtain the water-based zinc-rich coating.

8. The method for preparing a wear-resistant and corrosion-resistant water-based zinc-rich coating according to claim 7, characterized in that, In step two, the zinc powder has a fineness of 500-600 mesh.

Citation Information

Patent Citations

  • Waterborne epoxy zinc-rich coating and preparation method thereof

    CN117363157A

  • Preparation method of polyethylene glycol with terminal group containing furan ring

    CN105504264A

  • Quick-dry waterborne epoxy zinc-rich primer and preparation process thereof

    CN113429860A